Analisis Pengaruh Gender dan Status Perkawinan terhadap Produktivitas Karyawan Work From Anywhere (WFA) - Ferrinda Aprilia Kautsar Syaharani Hazmi; Diah Priharsari; Fajar Pradana (Fakultas Ilmu Komputer (FILKOM), Universitas Brawijaya, 2022)
Work From Anywhere is a form of adjustment for an organization or company to the COVID-19 pandemic which cannot be separated from digital transformation assistance and advances in information technology which more or less change the order and work culture of an organization or company. Currently, employee productivity is a priority for most companies because this is one of the factors for the company's success in the time of COVID-19. An employee is considered productive if his mental state continues to motivate him not to be easily satisfied and motivates him to continue to grow every day. This can be influenced by several factors, such as internal factors that grow close to the employees themselves. The purpose of this study is to determine the effect of gender and marital status on employee productivity while working from anywhere. Data collection was carried out using a mixed method for employees who are currently or have undergone Work From Anywhere through semi-structured interviews and distributing questionnaires. The data obtained from the interview results were analyzed using the thematic analysis method. While the data obtained from the results of distributing the questionnaires were analyzed using a different test using SPSS software. The results of this study are that gender differences have an influence on productivity and lead to gender-based company policies where this can increase productivity during Work From Anywhere. Furthermore, differences in marital status do not affect productivity, but lead to differences in work motivation which can increase productivity when Work From Anywhere.